GAMBARAN POLA ASUH DAN PERTUMBUHAN BALITA PENDERITA GIZI BURUK PASCA DIRAWAT DI RUMAH GIZI SEMARANG - Widayani, Marantina Diska; Kartasurya, Martha Irene; Pradigdo, Siti Fatimah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
In 2013 Semarang City was in the third positition among the highest of severe malnutrition in Central Java Province. Therefore Local Health office has built malnutrition clinic to treat severe malnutrition cases. The activities in this clinic aimed to alleviate malnutrition. The purpose of this study was to describe the knowledge, child care pattern, disease history, growth and nutrition intake of post-treated under five malnourished children in Semarang Nutrition Cinic. This study was a descriptive study. The subject were 25 treated severe undernourished under five year children at Semarang Nutrition Clinic in 2014. Data were collected by interviews using questionnaires, semi-quantitative Food Frequency Questionnaires (SQFFQ), and weight measurements. Data were analized and presented in the form of graphs and tables. Results showed that 80% mothers had good knowledge. All mothers get have less portion of food than needed, 72% mothers served unvaried food, 80% children had not complete immunization, 52% had diarrhea, 40% had upper respiratory tract infection, 24% had tuberculosis in the last 6 month. The average energy adequacy rate was (61.7+8.0)%, protein adequacy rate was (81.7+13.5)%, and fat adequacy rate (95.48+22.9)%. At post treatment at Nutrition clinic, the percentage of severe malnourished decrease into 52%, but after 6 months release from nutrition clinic, the number of severe malnourished children increased into 92%. It is concluded that after six months released from the nutrition clinic, the nutritional status of the children were decreased.